Infant Formula Supplemented With Milk Fat Globule Membrane, Long-Chain Polyunsaturated Fatty Acids, and Synbiotics Is Associated With Neurocognitive Function and Brain Structure of Healthy Children Aged 6 Years: The COGNIS Study - Nieto-Ruiz, Ana; García-Santos, José A.; Verdejo-Román, Juan; Diéguez, Estefanía; Sepúlveda-Valbuena, Natalia; Herrmann, Florian; Cerdó, Tomás; De-Castellar, Roser; Jiménez, Jesús; Bermúdez, Mercedes G.; Pérez-García, Miguel; Miranda, M. Teresa; et al. (Frontiers in Nutrition, 2022)
Background: Adequate nutrient intake during the first months of life plays a critical role on brain structure and function development. Objectives: To analyze long-term effects of an experimental infant formula (EF) on neurocognitive function and brain structure in healthy children aged 6 years, compared to those fed with a standard infant formula or breastfed. Methods: The current study involved 108 healthy children aged 6 years participating in the COGNIS Study. At 0-2 months, infants were randomized to receive up to 18 months of life, a standard infant formula (SF) or EF enriched with milk fat globule membrane (MFGM), long-chain polyunsaturated fatty acids (LC-PUFAs) and synbiotics; furthermore, a reference group of breastfed (BF) infants were also recruited. Children were assessed using neurocognitive tests and structural Magnetic Resonance Imaging (MRI) at 6 years old. Results: EF children showed greater volumes in the left orbital, higher vocabulary scores and IQ and better performance in an attention task, than BF children. EF children also presented greater volumes in parietal regions than SF kids. Additionally, greater cortical thickness in the insular, parietal and temporal areas were found in children from the EF group than those fed with SF or BF groups. Further correlation analyses suggest that higher volumes and cortical thickness of different parietal and frontal regions are associated with better cognitive development, in terms of language (verbal comprehension) and executive function (working memory). Finally, arachidonic acid (ARA), adrenic acid (AdA), docosahexaenoic acid (DHA) levels in cheek cells glycerophospholipids and ARA/DHA ratio, as well as proteins, fatty acids and minerals intake during the first 18 months of life, seem to be associated with changes in the brain structures at 6 years old. Conclusions: Supplemented infant formula with MFGM components, LC-PUFAs and synbiotics seems to be associated to long-term effects on neurocognitive development and brain structure in children at 6 years old.